Perfil socioeconômico dos catadores de materiais recicláveis organizados em cooperativas e associações do Espírito Santo - Guimarães, Julia Paula Soprani (2017)
Waste pickers are in the basis of recycling’s production chain and they are the main responsibles for the recovery of post-consumption dry residues in developing countries. Their inclusion in the solid waste management in Brazil was consolidated with the approval of the Brazilian Solid Waste Policy (BSWP) in 2010. However, general information and data about their socioeconomic status is still lacking, especially at municipal and/or regional level, which compromises the integrated urban solid waste management planning. For that matter, this work aims at tracing the socioeconomic profile of the waste pickers organized in cooperatives and/or associations in Espírito Santo, as well as assessing its relation to the main operational dysfunctions in the solidarity economy enterprises (EES). To accomplish this task, 24 EES (23 associations and 1 cooperative) located in five administrative microregions of the state have been selected and semi-structured questionnaires were applied to 215 of their associates in order to obtain information regarding their demographics, education, living and work conditions, and income. The results have showed that 60.5% of the associates are female, the minimum and maximum age ranges found were, respectively, 15 to 19 (0.9%) and 70 to 74 (2.3%). In regard to their education, 21.4% of the interviewed have claimed to be illiterate, 10.2% have not finished the first 4-year cycle of elementary school and 30,7% have an average of 5 to 8 years of schooling. Most of the waste pickers (61.8%) live in adequate and permanent private houses. Regarding their declared income, 57.7% earn more than a half to a minimum wage (R$ 441 to R$ 880) and 24.2% earn more than 1 to 2 minimum wages (R$ 881 to R$ 1,760), most of them (90.23%) fitting in the economy classes C2 and D-E. Besides, 46% depend exclusively on the income from the collective organization. The dysfunctions found to be related to their socioeconomic profile were: distrust of the companies and community in regard to the waste pickers, lack of specialized technical consultancy services, little knowledge about associativist culture, and lack of verticalization practices in the production process.